Caesar's Civil War - Batstone, William Wendell (Oxford approaches to classical literature., 2006)
Editors' Foreword. Preliminary Note. Introduction. 1. Choices: Genre, Content, Style. 2. Structure as Argument in Civil War. 3. Taking Sides, Making Sides. 4. Mastering Victory. 5. Writing Fighting War. Epilogue: Surviving Failure.